2005
DOI: 10.1016/j.ijid.2004.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus capitis endocarditis due to a transvenous endocardial pacemaker infection: Case report and review of Staphylococcus capitis endocarditis

Abstract: CoNS as a cause of endocarditis appears to be increasing and the current ability to determine the species of these organisms should elicit the epidemiology, clinical characteristics and biomolecular mechanisms involved in the induction of valvular disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 27 publications
0
27
0
3
Order By: Relevance
“…S. warneri, rarely associated with infection, has been occasionally noted as an etiologic agent of osteomyelitis, valve endocarditis, bacteremia, and urinary tract infections (9,53). S. capitis has been associated with bacteremia and infective endocarditis (12,51). Nonpathogenic staphylococci involved in food fermentation, e.g., S. carnosus, S. xylosus, S. equorum, S. arlettae, S. condimenti, and S. piscifermentans, are lysozyme sensitive and possess de-O-acetylated peptidoglycan.…”
Section: Discussionmentioning
confidence: 99%
“…S. warneri, rarely associated with infection, has been occasionally noted as an etiologic agent of osteomyelitis, valve endocarditis, bacteremia, and urinary tract infections (9,53). S. capitis has been associated with bacteremia and infective endocarditis (12,51). Nonpathogenic staphylococci involved in food fermentation, e.g., S. carnosus, S. xylosus, S. equorum, S. arlettae, S. condimenti, and S. piscifermentans, are lysozyme sensitive and possess de-O-acetylated peptidoglycan.…”
Section: Discussionmentioning
confidence: 99%
“…Staphylococcus aureus zazwyczaj wywołuje IZW o ostrym przebiegu, ze znaczną destrukcją zastawek, podczas gdy CoNS postać choroby o przedłużającym się przebiegu (poza S. lugdunensis [155] oraz niektórych przypadków S. capitis) [156,157]. W tabeli 17 podsumowano zalecenia dotyczące leczenia IZW wywołanego przez gronkowce złociste metycylinowrażliwe i metycylinooporne oraz CoNS zarówno na własnej zastawce, jak i u osób z protezą zastawkową.…”
Section: Staphylococcus Aureus I Inne Gronkowce Koagulazo-negatywneunclassified
“…Among non- epidermidis CoNS, Staphylococcus capitis is rarely, if ever, isolated from bacteremic adult patients [16]. Although this species has been occasionally reported in infective endocarditis cases [17], [18], it is most often considered to be a blood culture contaminant [16]. However, in the NICU setting, recent studies have indicated that methicillin-resistant S. capitis could emerge as a significant pathogen, causing LOS in VLBW infants [14], [19][22].…”
Section: Introductionmentioning
confidence: 99%